Knowledge of Culture and Heritage of India in Designing Marketing Campaigns - Palecanda, Siddhartha (Digital Repository of Theses, 2024)
The primary purpose of this study was to investigate the role of cultural and heritage aspects in shaping the consumer perceptions and brand dynamics within the marketing campaigns. The research aims to explore that how cultural and heritage related elements can be leveraged in order to design more effective and relevant marketing strategies, their impact on the performance of campaigns, Return on Investment (ROI), environmental and social well-being initiatives, and finally, the consumer engagement and brand perception. The study was based on the both primary and secondary data collection technique. In this, the primary data was collected with the help of structured questionnaire survey of various consumers of marketing campaigns using the simple random sampling technique. Total 105 respondents were surveyed with the help of emails, social media etc. The target area for this research was the southern states of India such as Karnataka, Tamil Nadu, Telangana, Andhra Pradesh and Kerala. On the other hand, the secondary data was collected from the obtained at the local chamber of commerce offices located in each temple town of southern India. For the purpose of data analysis both descriptive analysis, Correlation and Regression was used with the help of SPSS software. The findings reveal a strong positive correlation between the incorporation of cultural and heritage aspects and the perceived relevance, effectiveness, and performance of marketing campaigns. confirms the significant impact of cultural integration on campaign success, ROI, and consumer engagement. Brands strategically incorporating cultural elements witness higher ROI and enhanced consumer engagement, fostering deeper connections and brand loyalty. Moreover, campaigns integrating cultural narratives contribute to positive environmental and social well-being perceptions, aligning brands with societal values and fostering goodwill. In conclusion, this research suggests the cultural and heritage dimensions of contemporary marketing strategies are inherently transformative. Increasing campaign effectiveness by means of authentic cultural integration does not merely contribute to society’s aspirations but also fosters environmentalist and socially responsible objectives. The results have important implications for marketeers, underlining the importance of cultural responsiveness and relevance to connect with consumers from different segments effectively to establish long term brands.